Internal Market Orientation and Supply Chain Visibility as the Antecedent of New Product Flexibility: Exploring Moderating Impact of Internal Integration - Anuch Nampinyo; Piyamas Klakhaeng; Srisarin Suksutthi; Kittiampol Sudprasert (International Journal of Supply Chain Management, 2020)
Objectives of current study are to examine the impact of Supply Visibility, market orientation and supply chain responsiveness on new product flexibility. Moreover, moderating role of internal integration is being examined in the current study as well. For current research, data collection was done with help of structured questionnaire from the customers of electronic sectors of Indonesia. The response rate of the current study is 53.5% which is significantly higher than the threshold level of 30%. In this research, we used two-step process for analyzing and describing the data analysis outcomes obtained through PLS-SEM. The result indicates that the all path is significant at p-value less than 0.05, and integration appears as a significant moderator. The present study adds on the previous literature regarding under study constructs. The results of the study ensure that improvement in internal market orientation, supply visibility enhances responsiveness in supply chain, which in turn increases the flexibility in new product making. Current study focuses on new product flexibility as an outcome of internal market orientation, supply visibility. While aligning all these supply chain strategies will significantly impact to reduce unnecessary supply chain costs.